MANAGEMENT OF FLUCTUATION OF FINANCIAL AND ECONOMIC INTEGRATED DEVELOPMENT OF INNOVATIVE ENTERPRISE - K. S. Boichenko; M. A. Tepliuk; N. Yu. Rekova; I. I. Stashkevych; M. Morkunas (Фінансово-кредитна діяльність: проблеми теорії та практики)
The main purpose of this article is to study the fluctuation management of financial and economic performance of innovative enterprises’ activity comprehensively in the context of their effective integrated development. The study found that achieving a high level of management of integrated enterprise development by fluctuation indicators, is possible when evaluating the effectiveness of functioning on the basis of a range of methods of improvement  the quality management of integrated development of the enterprise on the fluctuation indicators, resource allocation in order to reduce the level of fluctuation of expectations in the process of integrated development between enterprise and stakeholders using a set of basic and additional features to ensure efficiency of the development management at a high level and corresponding changes in key indicators, as well as maintain the balance in the form of alternatives in the disturbing effects of internal and external environmental factors of the enterprise.